2019
DOI: 10.3390/ijms20215459
|View full text |Cite
|
Sign up to set email alerts
|

Monocytic Myeloid Derived Suppressor Cells in Hematological Malignancies

Abstract: In the era of novel agents and immunotherapies in solid and liquid tumors, there is an emerging need to understand the cross-talk between the neoplastic cells, the host immune system, and the microenvironment to mitigate proliferation, survival, migration and resistance to drugs. In the microenvironment of hematological tumors there are cells belonging to the normal bone marrow, extracellular matrix proteins, adhesion molecules, cytokines, and growth factors produced by both stromal cells and neoplastic cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 116 publications
7
21
0
Order By: Relevance
“…In accordance with previous studies [17,23,24], we found an increased frequency of M-MDSC in CLL patients in comparison to healthy controls. M-MDSC are also expanded in the peripheral blood of freshly diagnosed patients with Hodgkin's lymphoma, follicular lymphoma, diffuse large B-cell lymphoma, and other haematological malignancies [18]. Consistent with our study, Liu et al revealed that M-MDSC cells are associated with the CLL clinical stage [25].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with previous studies [17,23,24], we found an increased frequency of M-MDSC in CLL patients in comparison to healthy controls. M-MDSC are also expanded in the peripheral blood of freshly diagnosed patients with Hodgkin's lymphoma, follicular lymphoma, diffuse large B-cell lymphoma, and other haematological malignancies [18]. Consistent with our study, Liu et al revealed that M-MDSC cells are associated with the CLL clinical stage [25].…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, the percentage of M-MDSC in the peripheral blood of various indolent lymphomas (mostly follicular lymphomas) is significantly higher when compared to healthy controls, while being significantly lower than in more aggressive lymphomas [16,17]. In addition, a monocytic subset of MDSC (CD14 + HLA-DR low ) is increased in CLL (chronic lymphocytic leukaemia) patients and has a capacity to inhibit T cell activation, as well as induce Treg via IDO [18]. Concurrently, no difference was observed in mycosis fungoides [19] and Waldenström macroglobulinemia [17].…”
Section: Introductionmentioning
confidence: 99%
“…During tumor microenvironment (TME), MDSCs suppress the host anti-tumor immune response through inhibition of T cell proliferation, cytokine secretion, and recruitment of regulatory T cells in hematological malignancies. In all hematological malignancies, several strategies to target MDSCs could improve immune therapies via multiple mechanisms, such as hampering MDSCs function, promoting MDSCs maturation, and depleting MDSCs [82][83][84]. HMGB1 can facilitate MDSCs differentiation in BM and inhibit the activation of antigen-driven CD4 + and CD8 + T cells.…”
Section: Hmgb1 and The Inflammatory Bone Marrow Microenvironmentmentioning
confidence: 99%
“…The accumulation of MDSCs has been demonstrated in many types of human solid tumors [6]. However, the relevance of this heterogeneous population in hematopoietic malignancies has only recently gained stronger attention [7][8][9][10]. MDSCs are a phenotypically and functionally heterogeneous group of cells.…”
Section: Introductionmentioning
confidence: 99%
“…The leukemic B cells achieve this mainly through the involvement of regulatory T (Treg) cells. In turn, MDSCs release IL-10 and TGF-b to exert their suppressive function by Tregs [8,20]. The origin of M-MDSC is unknown.…”
Section: Introductionmentioning
confidence: 99%